PENGARUH PERMAINAN BOCCE TERHADAP PENINGKATAN MOTORIK KASAR ANAK TUNAGRAHITA SEDANG di SLBN 2 PADANG - putra, rian ananda (journal of residu, 2019)
Children with intellectual disabilities are having problems in physical and motor development. Developmental retardation children, especially mentally retarded children, show symptoms of lack of coordination in motion activity that is indicated in the response of the muscles and movements with a low pattern and less varied. Gross motor skills are basically the first step to being able to master more detailed skills, namely fine motor skills. One effort to train the mental motor skills of mentally retarded children is by playing or by sports. Therefore, researchers try to use bocce games as a medium to improve gross motor skills. Where in the bocce game there are movements that can improve gross motor skills especially hand movements in the ability to throw, push, and lift weights. The purpose of this study was to see how the influence of the bocce game on the gross motor abilities of mentally retarded children is the type of research used is Single Subject Research with A-B-A design. Based on data processing, the obtained baseline-1 (A-1) mean in subject A was 667%, mean intervention (B) in subject A was 75.2%. And the mean baseline (A-2) in subject A is 68.3%. So it can be concluded that the bocce game can improve gross motor skills in children with mental retardation. For this reason, educators should be able to apply the bocce game in an effort to train and improve basic motor skills in students. .